Proton magnetic resonance spectroscopic analysis of changes in brain metabolites following electroconvulsive therapy in patients with major depressive disorder - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2020)
Objectives: The aim of this study was to evaluate the metabolic changes in the anterior cingulate cortex (ACC) induced by electroconvulsive therapy (ECT) in patients with MDD via H-1-MRS. Methods: The study was conducted on 13 MDD patients receiving ECT treatment and 14 healthy controls matched in terms of age, gender and education. The patients underwent six sessions of ECT. H-1-MRS imaging and psychometric evaluations obtained before 1st and after the 6th sessions. The control group also went through the same procedures except for ECT. N-Acetyl aspartate (NAA), choline (Cho) and creatine (Cr) metabolite levels and the creatine to metabolite ratios were measured. Results: There was no significant difference in the ACC metabolite levels of the patients and those of the controls at the baseline. ECT associated with a statistically significant decrease in the NAA/Cr ratio in ACC. All of the patients had responded to ECT treatment as measured with the clinical scales. Conclusions: The results has suggested that indirect proof of an increase in energy metabolism without any evidence of impaired neuronal viability in the ACC induced by ECT. The relative increase in Cr levels following ECT in MDD seems to be associated with improvement in clinical severity.
Keywords: MDD; ECT; H-MRS; ACC; NAA; creatinine; choline; ABNORMALITIES; HIPPOCAMPUS; UNIPOLAR; CORTEX; RISE